DOI: 10.33915/etd.5988
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of an Exercise and Kinesiotape Intervention on Forward HeadRounded Shoulder Posture and Scapular Dyskinesis

Abstract: Context: Forward head and rounded shoulder posture as well as scapular dyskinesis are forms of improper posture that have been linked to neck and shoulder pain. Treatment for forward head posture (FHP), rounded shoulder posture (RSP), and scapular dyskinesis has consisted of an exercise protocol. Kinesiotape (KT) has recently been used as a treatment method but there is a lack of research on the effectiveness, or whether exercise or KT is better than the other. Objective: The objective of the study was to comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 41 publications
(369 reference statements)
0
3
0
Order By: Relevance
“…There were 12 studies in which 2D techniques were used to investigate effects of exercise on scapular position and motion. 3,10,18,20,27,29,31,32,36,[38][39][40] The findings revealed that regardless of the challenging reliability of the measurement technique, most studies showed significant sources of bias. For example, Roddey et al 36 reported a significant effect of pectoralis minor stretching on TSD.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…There were 12 studies in which 2D techniques were used to investigate effects of exercise on scapular position and motion. 3,10,18,20,27,29,31,32,36,[38][39][40] The findings revealed that regardless of the challenging reliability of the measurement technique, most studies showed significant sources of bias. For example, Roddey et al 36 reported a significant effect of pectoralis minor stretching on TSD.…”
Section: Discussionmentioning
confidence: 98%
“…There were 8 studies among the 20 included papers in which 3D techniques were used to evaluate effects of therapeutic exercises on scapular kinematics 6,12,22,28,37,42,45,46 ; the other 12 studies used 2D techniques to record scapular motions. 3,10,18,20,27,29,31,32,36,[38][39][40] In addition, in 3D or 2D techniques, each researcher chose different devices and setups to record the scapular motion. Considering the fact that the reliability of measurements with different devices varies widely, controversy in the results of the studies seems reasonable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation